Schooling Forsaken: Education and Migration - Ilhom Abdulloev; Gil S. Epstein; Ira N. Gang (Institute of Labor Economics (IZA), 2019)
We examine the phenomenon of forsaken schooling resulting from opportunities abroad. The brain-drain/gain literature takes as its starting point the migration of educated/professional labor from poor origin countries to richer host countries. While high-skilled migration is worrisome, many international migrants accept low-skilled positions in host countries. Their willingness to do so arises from very large host-home earnings differentials. At home this can lead to reduced educational investment as people forgo schooling because of opportunities to migrate to high paying low-skilled jobs. This suggests possible time-inconsistencies between short-run economic gains from migration and negative long-term effects from missing human-capital investment. We analyze data from Tajikistan, where approximately one-third of the labor force works outside of the country. We offer an explanation of our empirical results with a theoretical model, allowing us to establish the circumstances under which this type of forsaken schooling can occur and the trade-offs that policymakers' need consider.
Keywords: O15; P46; F22; I24; 330; migration; traps; poverty; inequality; education; skill